Legitimacy and Multilevel Governance in the European Union: Challenges for Integration in the 21st Century - Benedetti, Christopher Paul (My University, 2001)
Placed within the context of the dynamic relationship that exists between state-level actors, supranational institutions, and individual citizens in Europe, this analysis endeavours to examine some of the main issues surrounding European integration theory, the institutionalisation of the European Union, and the so-called 'democratic deficit'. While recognising that much of the debate surrounding multilevel governance in Europe has traditionally focused upon the effects convergence has and will continue to have on predominantly state-level variables, it is my contention that centralised political institutions in European are bound to endure perpetual mismanagement and a lack of majority individual support should the integration process continue down the path of political integration and 'polity'-building without first resolving inherent legitimacy problems. Furthermore, without entrenching the necessary foundations of legitimate governance within the integration process, political allegiance to the European Union will never be able to achieve the same level of tacit support amongst individuals as primary allegiance to the nation-state. The analysis thus focuses on how European integration and 'supranationalism' has affected the relationship that exists between individual citizens and decision-makers at the 'European' level, vis-a-vis democracy, accountability, transparency and accessibility. An assumption is first made that legitimacy' in governance flows from the existence of strong democratic linkages between individual citizens and their decision-makers (vis-a-vis output, input and social legitimacy). Building heavily upon the work of Held, Schmitter and Dahl, the thesis compares the institutional structure of the EU to a model of 'legitimate' democratic governance. It also raised questions concerning the transferability, to the supranational level, of state-centred theories of democracy and representation, and challenges several approaches to understanding the place of 'identity' and Putnam's 'social capital' and 'trust' in polity-building. To accomplish this task, a normative and functional evaluation is conducted on the 'nature' of the European Union and its institutions (intergovernmentalism vs. supranationalism). Milward's definition of 'allegiance' is also particularly helpful in describing the multi-layered characteristic of individual identification towards different levels of national and supranational governance, especially in a European context.
Following the theoretical portion of the analysis, a closer examination is made of the institutions of the European Union and their respective levels of transparency and accountability. As a case study, the Report of the Committee of Independent Experts to the European Parliament (March 1999) is used to show how ineffective some of the institutions, namely the European Commission, have been at resolving perceived accountability problems. The thesis suggests how core institutions may be reformed, as well as alternatives to the current structure of the Union's activities. The analysis then concludes by focusing on how legitimate structures of governance have been jeopardised in Europe, and how the integration process has, and continues to, place the advantages accrued through economic harmonisation and policy convergence ahead of the need for political stability and the entrenchment of strong, democratic institutions at the supranational level.
Keywords: state level; institutions; individual citizens; Europe; integration theory; European Union